2019
DOI: 10.1002/adfm.201808462
|View full text |Cite
|
Sign up to set email alerts
|

Linear Chimeric Triblock Molecules Self‐Assembled Micelles with Controllably Transformable Property to Enhance Tumor Retention for Chemo‐Photodynamic Therapy of Breast Cancer

Abstract: Although nanoparticles are expected to revolutionize cancer treatment, their low efficacy remains the greatest limiting factor. Recent investigations found that nanoparticles' golden principle, the enhanced permeability and retention (EPR) effect, is limited by the complicated tumor microenvironment. Herein, novel transformable nanomaterials are designed to utilize the EPR effect more effectively. By tandem conjugation of the hydrophobic head (chlorin e6 (Ce6) or bilirubin (BR)), peptide to form hydrogen bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 62 publications
1
67
0
Order By: Relevance
“…[ 1 ] However, the use of chemotherapeutics, such as irinotecan and topotecan derivatives, which are camptothecin (CPT) analogs, is disadvantageous because of uncontrolled release behavior and poor targeting ability, which easily induce systemic toxicity, immunosuppression, and drug resistance. [ 2 ] To date, numerous studies have confirmed that combined therapy holds promising prospects in cancer treatment. [ 3 ] Notably, photodynamic therapy (PDT), a non‐invasive method for cancer therapy, can generate reactive oxygen radicals (ROS) under light irradiation, which causes irreversible damage to tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] However, the use of chemotherapeutics, such as irinotecan and topotecan derivatives, which are camptothecin (CPT) analogs, is disadvantageous because of uncontrolled release behavior and poor targeting ability, which easily induce systemic toxicity, immunosuppression, and drug resistance. [ 2 ] To date, numerous studies have confirmed that combined therapy holds promising prospects in cancer treatment. [ 3 ] Notably, photodynamic therapy (PDT), a non‐invasive method for cancer therapy, can generate reactive oxygen radicals (ROS) under light irradiation, which causes irreversible damage to tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transformable linear chimeric triblock molecules Ce6/BR-FFVLK-PEG were designed by our lab 18 . The hydrophobic head [chlorin e6 (Ce6) or bilirubin (BR)], and hydrophilic tail [polyethylene glycol (PEG)] were tandem conjugated with Phe-Phe-Val-Leu-Lys (FFVLK) for forming spherical micelles.…”
Section: Introductionmentioning
confidence: 99%
“…For conventional nanoparticles, their circulation time, cellular uptake, and in vivo tissue distribution are mainly controlled by various factors, such as diameter, shape, surface charge, and rigidness [1,33,34]. For instance, micro-sized, long, flexible filomicelles could not be internalized by macrophages and have a very long circulation of days or even weeks [35].…”
Section: Introductionmentioning
confidence: 99%